Carabid diversity in alpine environments: Investigating biogeographic and ecological traits of the communities living in the Dolomites (Italy) - Roberto PIZZOLOTTO (European Journal of Entomology)
In the landscape of the Dolomites, within the protected area of the Paneveggio - Pale di S. Martino Park in the Eastern Alps of Italy, a study was conducted to explore the distribution of carabid beetles. To achieve this, pitfall traps were placed along a 1000-m elevation gradient, following the bioclimatic gradient from spruce forests to the resilient pioneer vegetation in the extreme high-altitude environments. The research revealed that both community diversity and biogeographic diversity exhibited a clear correlation with the bioclimatic gradient. As one ascended to higher altitudes, the composition and distribution of carabid beetle communities shifted, reflecting the bioclimatic gradient. The chorological spectrum of the communities showed that Pleistocene paleoclimatic events provided the triggering factors affecting the postglacial recolonization of alpine ecosystems of the Dolomites region. Most of the sampled species displayed specific life strategies that enabled them to thrive in this harsh setting, responding to the selective pressures imposed by ecological factors. An extensive dataset encompassing the diversity of carabid beetles in these high-altitude domains was created. Given that the studied environments are widely distributed along the Italian Eastern Alps, the dataset serves a crucial purpose as it can be used as a reference for other research campaigns conducted in similar environments. Furthermore, it could act as a temporal benchmark for future researches on insects living in extreme environments, e.g. the Dolomites, or for comparing changes in climate that may be detected by future studies in the same geographic area.